A Bibliometric Analysis of Tax Avoidance Research in Indonesia - Maulana, Ilham; Jufri, Achmad (Universitas Airlangga, 2025)
Background: Tax avoidance in Indonesia significantly impacts state revenues and public trust in the tax system. Despite various tax reforms to improve efficiency, administrative complexity and low compliance persist. Bibliometric analysis is crucial for evaluating research development and trends, offering insights into influential studies, authors, and gaps in tax avoidance research. Objective: This study aims to provide a comprehensive overview of tax avoidance research in Indonesia through bibliometric analysis, identifying research trends, influential authors, and gaps in the existing literature. Method: The study employs bibliometric analysis to collect and analyze data on tax avoidance in Indonesia from scientific publications. It includes citation analysis, network analysis, and data visualization using tools like Bibliometrix and VOSviewer to uncover research patterns and trends. Results: The analysis reveals significant growth in tax avoidance research in Indonesia. It identifies various factors influencing tax avoidance behaviour, methods used by taxpayers, and the impact on the economy and tax system. The study highlights the most productive authors and institutions, frequently discussed topics, and collaboration networks among researchers. Conclusion: The bibliometric analysis offers a detailed and contextual understanding of tax avoidance research in Indonesia. It highlights strengths and weaknesses in the literature and provides recommendations for future research, focusing on issues relevant to the Indonesian context. This study aims to support policymakers, academics, and practitioners in developing strategies to combat tax avoidance and enhance tax compliance. Keywords: Bibliometric; Bibliometrics; VOSviewer; Tax Avoidance.